Accelerated thrombolysis in a rabbit model of carotid artery thrombosis with liposome-encapsulated and microencapsulated streptokinase - Leach, J. Kent; O’Rear, Edgar A.; Patterson, Eugene; Miao, Yiwei; Johnson, Arthur E. (Thrombosis and Haemostasis, 2003)
The present study compares the efficacy of two formulations of encapsulated streptokinase to streptokinase in a rabbit model of carotid artery thrombosis. Arterial thrombosis followed the injection of thrombin mixed with autologous whole blood into a carotid artery of New Zealand white rabbits. Thirty minutes after the confirmation of an occlusive thrombus, one of four streptokinase formulations was infused at a dosage of 6,000 IU/kg into the jugular vein. Free streptokinase (FREE SK) was compared to identical dosages of streptokinase encapsulated in a liposome (LESK), streptokinase entrapped in a water-soluble polymer (MESK), and free streptokinase admixed with blank microparticles (FREE SK + BLANK). Carotid arterial blood flow was determined by pulsed Doppler flowmetry to confirm clot formation and reperfusion. Two hours after drug infusion, the rabbits were killed and the residual thrombus mass was determined.Compared to FREE SK (74.5 ± 16.9 min; mean ± SEM), LESK demonstrated significantly reduced reperfusion times (19.3 ± 4.6 min) while MESK exhibited even greater improvement (7.3 ± 1.6 min). FREE SK + BLANK showed no statistical improvement versus FREE SK. LESK and MESK also resulted in reduced residual clot mass and greater return of arterial blood flow. These studies suggest that encapsulation of streptokinase offers a potential method of improved fibrinolytic treatment for patients with clot-based disorders. MESK performed slightly better than LESK with improved production and storage characteristics.
Keywords: Thrombolytic therapy; streptokinase; microencapsulation; liposomes; thrombus